School Organizational Culture, Family Background, School Environment as Determinants of Students’ Academic Performance in Selected Secondary Schools in Meru District, Arusha, Tanzania - Tarimo, Valentine (IJRDO - Journal of Social Science and Humanities Research, 2020)
This study assessed the influence of school organizational culture, family background and school environment variables as determinants students’ academic performance in selected secondary schools in Meru District, Arusha, Tanzania. Five secondary schools in Meru District Council were selected for this study. The study hypotheses were: (H1) School organization culture is positively correlated with students’ academic performance in Meru secondary schools, (H2) family background is positively correlated with students’ academic performance in Meru secondary schools and (H3) school environment is positively correlated with students’ academic performance in Meru secondary schools. The study employed correctional cross-sectional design. A sample size of four hundred respondents was randomly chosen from five selected secondary schools in Meru district. A self-administered questionnaire was used to collect information from respondents. The collected data were analysed by Statistical Package for Social Scientists using, Independent t-test and Fisher’s Analysis of Variance to determine whether demographic variables vary with students’ academic performance. Karl Pearson’s Linear Correlation Coefficient was undertaken to assess the correlation between school organization culture, family background, school environment and students’ academic performance. The study results indicated that, all three study hypotheses were supported by the findings that school organization culture, family background, school environment was statistically significantly positively correlated with students’ academic performance in Meru secondary schools. The study concluded that, organization culture, family background, the school environment priority which found to have significant influenced students’ academic performance.